Eosinophilic esophagitis. - Couto, Mariana (2011)
Eosinophilic esophagitis (EE) is an inflammatory disease of the esophagus characterized by significant and isolated infiltration of the esophageal mucosa by eosinophils, associated with clinical symptoms of esophageal dysfunction, affecting children and adults. It is an increasingly frequent cause of symptoms similar to gastroesophageal reflux disease but refractory to anti-acid therapeutic. It is commonly associated with food allergies or other atopic diseases. Since there are no symptoms, signs, serological biomarkers or endoscopic findings pathognomonic of EE, the diagnosis requires a high degree of suspicion; moreover, due to its chronic relapsing nature the potential to cause major esophageal structural changes, its early recognition and close cooperation between gastroenterologists and immunoallergologists is essential for the timely institution of appropriate therapy. The treatment is based on two main strategies: diet and / or pharmacotherapy, depending on the co-existence of sensitization to food allergens. It is our aim to review this issue, considering recent guidelines, as well as propose a diagnostic and therapeutic algorithm.